Respuesta :
Answer:
2x^2 + 6x - 4.
Step-by-step explanation:
This is 3x^2+ x - 3 - (x^2 - 5x + 1) (Note we put the last function in brackets).
Distributing the negative over the brackets:
3x^2 + x - 3 - x^2 + 5x - 1
= 2x^2 + 6x - 4 (answer).
Answer: The correct option is
(D) [tex]f(x)-g(x)=2x^2+6x-4.[/tex]
Step-by-step explanation: We are given the following two functions :
[tex]f(x)=3x^2+x-3,\\\\g(x)=x^2-5x+1.[/tex]
We are to find the expression for f(x) - g(x).
We have
[tex]f(x)-g(x)\\\\=(3x^2+x-3)-(x^2-5x+1)\\\\=3x^2+x-3-x^2+5x-1\\\\=2x^2+6x-4.[/tex]
Thus, [tex]f(x)-g(x)=2x^2+6x-4.[/tex]
Option (D) is CORRECT.